2019
DOI: 10.1002/cb.1750
|View full text |Cite
|
Sign up to set email alerts
|

Go big or go home: Risk seeking for experiential choices

Abstract: In decision making under risk, do consumers evaluate intangible, experiential options in a choice set in the same way they evaluate tangible, material options? Prior research on prospect theory, typically using either monetary or material objects as choice options, demonstrates that consumers are risk averse for choices involving gains, with a fairly robust tendency to favor a more certain outcome even when that outcome is less desirable. The present research focuses on decision making under risk for experient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
(128 reference statements)
1
7
0
Order By: Relevance
“…We, therefore, predict that trait transfer can offer a competitive and positive path (the mediating path in Panel 2 of Figure 1 visualizing our conceptual model) through which knowledge about prior users can result in increased experiential satisfaction. This prediction is unique to experiential and not product satisfaction judgments and is supported by previous research into satisfaction demonstrating that consumers can differentiate between product and experiential satisfaction (i.e., Mittal et al, 2019). Consistent with our prediction, prior work has shown that contagion can improve experiential satisfaction when the previous user had positive traits (i.e., Shen et al, 2021).…”
Section: Hypothesis Developmentsupporting
confidence: 88%
“…We, therefore, predict that trait transfer can offer a competitive and positive path (the mediating path in Panel 2 of Figure 1 visualizing our conceptual model) through which knowledge about prior users can result in increased experiential satisfaction. This prediction is unique to experiential and not product satisfaction judgments and is supported by previous research into satisfaction demonstrating that consumers can differentiate between product and experiential satisfaction (i.e., Mittal et al, 2019). Consistent with our prediction, prior work has shown that contagion can improve experiential satisfaction when the previous user had positive traits (i.e., Shen et al, 2021).…”
Section: Hypothesis Developmentsupporting
confidence: 88%
“…That appears to be the case, because consumers state that they are more comfortable making experiential purchases than material purchases without having all of the potentially relevant information available to them and they are more open to unforeseen elements of experiential purchases (Gallo, Jampol, Rampullo, & Gilovich, ). In addition, consumers exhibit decreased risk aversion (i.e., have a preference for less certain but more desirable options) for experiential offerings such as vacations or live events, while exhibiting the usual strong risk aversion (i.e., a preference for more certain yet less desirable options) for material offerings (Mittal et al., ). Indeed, the very meaning of the word “surprise” is different and carries more positive connotations, when considered in the context of experiential purchases than when considered in the context of material goods (Gallo, Jampol, et al., , Study 3).…”
Section: How People Evaluate and Choose Experiential And Materials Purmentioning
confidence: 99%
“…Others have examined additional consequences of consuming one purchase type versus the other, such as the promotion of gratitude (Walker et al., ), the triggering of envy (Lin, van de Ven, & Utz, ), or the elicitation of different types of regret (Goodman & Lim, ; Rosenzweig & Gilovich, ; Ruttan, ). Still others have been concerned with different aspects of consumer psychology (such as the influence of uncertainty, different styles of decision making, or the impact of word of mouth recommendations) and have documented important differences depending on whether the consumer is interested in an experience or a material possession (Gallo & Gilovich, ; Gallo, Sood, Mann, & Gilovich, ; Mittal, Kapitan, & Silvera, ; Pchelin & Howell, ; Tully, Hershfield, & Meyvis, ). Thus, 15 years after the publication of the seminal work on experiential versus material purchases, the amount of research in this field is vast.…”
Section: Introductionmentioning
confidence: 99%
“…Because of high interitem reliability (Cronbach’s α = .89), we averaged the three items and formed an aggregate measure of anxiety. Given the unknowns, choosing the mystery option could be inherently risky, and as such, the differential risk-taking tendencies might have affected the trade-offs (Mittal et al, 2019). We tapped into this alternative mechanism by using the previously mentioned 7-point scale to measure the extent to which participants pursued “risk” and “danger” when choosing between the two options.…”
Section: Methodsmentioning
confidence: 99%